Rekonstruksi Negara Hukum dalam Paradigma Hukum Islam dan Ketatanegaraan di Indonesia - Zulfahmi Nur (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2023)
This paper aims to analyse the discourse of the rule of law in the perspective of Islamic law and constitutional law in Indonesia. The research is a literature study with the main source of books, journals and other references related to the concept of the state in the perspective of Islam and constitutional law in Indonesia. The research method is descriptive qualitative with a normative approach. In the Indonesian context, the concept of law and the rule of law must be realised that it is not an original result or does not grow from within Indonesian society itself. The rule of law is an imported product or a building imposed from outside. The rule of law is the fruit of adoption and transplantation through the Dutch colonial concordance politics and European countries, commonly known as the Rule of Law and Rechtstaat. The conception of the Rule of Law and Rechtstaat are two conceptions of the rule of law that are only normative-legalistic in nature with categorical elements such as the supremacy of law, equality before the law, due process of law, It appears that the Indonesian rule of law, both at the level of the Rule of Law and Machtstaat, is influenced by external legal thinking that emphasises the anthropocentric dimension that focuses on individual and liberal values. So that in practice the Rule of Law turns into the Rule of Man, or from Rechtstaat turns into Machtstaat. In contrast to nomocracy in Islamic law, the rule of law is built on divine values, where law is the highest supremacy in human life. To get to the true state of law, it is necessary to reconstruct the conception and paradigm of the state of law in the future.